Movement proficiency and talent development in sport - Malina, R. M. (Journal of Kinesiology and Exercise Sciences, 2015)
The development of proficiency in movement skills is a major development task from childhood through adolescence. Proficiency in movement skills is also central to play behavior, to informal and formal games, and to sport-specific skills and functional capacities (power, speed, agility, strength, aerobic capacity, etc.). The teaching and refinement of sport-related skills is an objective of youth sport programs in general and of talent programs for specific sports. The development of movement proficiency is discussed in general and then in the context of talent development models and specifically the Long Term Athlete Development model. Four features of the talent development need to be recognized: (1) it is a dynamic and highly individualized process; (2) the process is superimposed upon a constantly changing base - the demands of physical growth, biological maturation and behavioral development, and their interactions; (3) the process is selective and exclusionary; and (4) fourth, although talent models view the process as long term, paths to elite status are highly variable among individuals.